Challenges and Opportunities for Regeneration in the Peripheral Nervous System - Höke, Ahmet (2009)
Regeneration in the peripheral nervous system offers unique opportunities and challenges to medicine. Compared to the central nervous system, peripheral axons can and do regenerate resulting in functional recovery, especially if the distance to target is short as in distal limb injuries. However, this regenerative capacity is often incomplete and functional recovery with proximal lesions is limited. Furthermore, regeneration of axons to the appropriate targets remains a challenge with inappropriate reinnervation being an impediment to full recovery. The reviews and selected original research papers in this Special Issue will address some of these challenges and highlight new opportunities for development of effective therapies for nerve regeneration.